1969
DOI: 10.1002/ijc.2910040109
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte destruction and ovarian tumorigenesis after direct application of a chemical carcinogen (9:10‐dimethyl‐1:2‐benzanthrene) to the mouse ovary

Abstract: Ovaries of immature mice were painted with 9:IO-dimethyl-l:2-benzanthracene ( D M B A ) , and the effect of the carcinogen on the number of oocytes as well as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

1969
1969
2012
2012

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 13 publications
2
27
0
1
Order By: Relevance
“…This finding of the present study conforms with the observations of Krarup (1970a) and Krarup and Loff (1971). Depletion of the oocytes by DMBA treatment is followed by ovarian tumorigenesis (Krarup, 1967(Krarup, , 1970b.…”
Section: Discussionsupporting
confidence: 96%
“…This finding of the present study conforms with the observations of Krarup (1970a) and Krarup and Loff (1971). Depletion of the oocytes by DMBA treatment is followed by ovarian tumorigenesis (Krarup, 1967(Krarup, , 1970b.…”
Section: Discussionsupporting
confidence: 96%
“…Ongoing apoptosis or necrosis and decreases in the reserve pool of small follicles usually are detectable by qualitative microscopic examination. Degeneration of oogonia in utero or in the immediate postnatal period may cause significant depletion of primordial follicles that would likely be further exacerbated in adults due to continued recruitment for growth from the already depleted primordial pool (Mandl and Zuckerman, 1952;Krarup, 1969;Murphy and Beamer, 1973;Hirshfield, 1994). These changes are discernible to a pathologist conducting a focused qualitative examination of the ovary.…”
Section: Qualitative Assessment Of the Ovarymentioning
confidence: 99%
“…A number of studies have shown that exposure to ovarian toxicants can lead to oocyte destruction Krarup et al, 1967;1969;1970;Maronpot, 1987;Melnick et al, 1990). How these effects are produced is becoming better understood and detailed for a number of chemical classes discussed herein.…”
Section: Impact Of Environmental Chemical Exposures On Follicular Atrmentioning
confidence: 99%